An Unusual Clinical Presentation of Solitary Fibrous Tumor in the Oral Cavity. (23rd February 2017) - Morais, Everton Freitas de; Moreira, Deborah Gondim Lambert; Oliveira, Viviane Alves De; Rodrigues, Rodrigo Rodrigues; Germano, Adriano Rocha; Freitas, Roseana de Almeida
Abstract : Solitary fibrous tumor is a rare neoplasm of mesenchymal origin that usually affects the pleura. This rarity becomes more relevant in the oral cavity since the clinical features are nonspecific. A 66-year-old female patient presented with a 3-month history of a swelling in the floor of the mouth, measuring 2 cm in greatest diameter, and pain symptomatology. Occlusal and panoramic radiographs showed no bone involvement. Ultrasonography of the submandibular and parotid salivary glands revealed normal morphology, dimensions, and echogenicity. During this exam, a nodular image of low echogenicity measuring about 2.7 × 1.8 cm was detected. An excisional biopsy was performed and histopathological analysis revealed a well-defined tumor-like lesion with alternation between hypercellular areas without a defined pattern and hypocellular areas. On immunohistochemistry, the tumor was positive for CD34 and CD99 and negative for α -SMA, S-100, and bcl-2. Combining the histopathological and immunohistochemical features, the diagnosis was solitary fibrous tumor. The patient is under periodical clinical follow-up and shows no signs of recurrence 7 months after surgical excision of the tumor. The combination of clinical-pathological and immunohistochemical features is necessary for the diagnosis.